Metastastic Melanoma in a Goat - de Melo-Neto, Gabriel Barbosa; de Barros Correia, Davi Alexandre; de Mesquita, Emanuela Polimeni; Araújo Torres, Márcia Bersane de Medeiros (Acta Scientiae Veterinariae, 2019)
Background: Melanoma is one of the 5 neoplasia types of that most frequently affect skin and subcutaneous tissue, es-pecially in Northeastern Brazil, where there is a high incidence of solar rays. It is a tumor that affects melanocytes and is characterized by diverse morphologies ranging from round to polygonal cells, including epithelioid cells, spindle cells, star-shaped or with a mesenchymal appearance, and presenting large amounts of melanin in the cytoplasm. The pigment can be found in the cytoplasm of macrophages, indicating the phagocytic activity at the site. The nucleus is basophilic, and mitotic figures are not numerous. Case: A 12-year-old female goat with a history of nodular lesion in the nasal region with progressive increase and recur-rence was submitted to clinical evaluation. The tumor presented suggestive characteristics of melanoma, such as elevated irregular and surface with a central region of black colored skin. After surgical removal of the nodule, recurrence was observed in infra-orbital and parotid regions with infiltration of the mandible. Hence, the malignant behaviour of the tumor indicated euthanasia of the animal. The owner authorized the procedure and the individual was then submitted to necropsy at the Animal Pathology Sector of the Federal Rural University of Pernambuco, Academic Unit of Garanhuns (UAG/UFRPE). At necropsy, findings included a tumor in the parotid region with infiltration to the mandible, multiple tumors of black or grayish-white color in liver, multifocal nodules of grayish color in the right kidney and left kidney also had tumors of the same colorations, in the thoracic cavity, blackened spots were observed in the sternum. The lungs had several black colored nodules distributed throughout the organ. Microscopic examination revealed metastatic cells with intracytoplasmic brown pigments, in addition to granular and pleomorphic aspect. The lymph nodes presented the higher number of metastatic foci. Tumor cells were observed in metastatic nodes surrounded by disorganized tissue in organs, such as liver, right kidney, mandible and lungs. Discussion: The diagnosis was concluded based on the metastatic foci found in the several organs along with macroscopic aspects of the tumors and the histopathological evaluation. In addition, the findings were also confirmed with data found in the scientific literature. The clinical evolution and the appearance of new metastatic foci in only three weeks indicated that it was a tumor with a high degree of invasiveness. The evolution period was shorter than the reports described in the literature. Also in an unusual manner, the numerous metastatic foci in several organs compromised the general status of the animal. The involvement of the liver and lung parenchyma by the tumor, considerably diminishing the functionality of these organs, and the macroscopic characteristics with darkened aspect, microscopically correspond to areas of metastatic foci. The histopathological evaluation of the white or yellow areas revealed necrosis with adjacent tissue disorganization. The alterations described in the kidney, sternum and mandible were also described in the literature as possible sites of metastasis. However, there are few reports describing elevated numbers of metastases in a single animal, and in such rich detail with macroscopic and microscopic records, allowing the conclusion of this case as a malignant melanoma.